Christian Students' Sexual Behavior and Their Religious Beliefs in Ghana, West Africa - Dwamenah, Anúm (Journal of Philosophy, Culture and Religion, 2023)
Purpose: The purpose of this study was to establish the influence of religiosity among Christian high school students in West Africa. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low-cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Results: The results revealed that there exist conceptual and contextual gaps relating to the study on the influence of religiosity among Christian high school students in West Africa. Preliminary empirical review reveals that 40% of the students had had sex, 58% of whom did not use a condom. The study also found no relationship between religiosity and sexual behaviour of high school students (r=-.322, p>.05). A majority (94.7%) of the students felt that counselling was appropriate in addressing sexual behaviour among them. Unique Contribution to Theory, Practice and Policy: Holton's conflict management model, human need theory and reconciliation theory may be used to anchor Christian students' sexual behaviour and religious beliefs. This study's findings may provide insight on the importance of religion in encouraging sexually responsible behavior in young people. The results may suggest that religious adolescence programs are a viable option for guiding young people's sexual behavior. Researchers hope their findings may inspire new approaches to adolescent sexuality counseling that draw on religious belief systems as a resource. The findings of this research could be used by religious authorities to develop programs aimed at teen sexuality in religious settings.